PENGARUH PEMBERIAN SILASE CAMPURAN RUMPUT DAN DAUN MARKISA HUTAN DENGAN PROPORSI YANG BERBEDA TERHADAP TINGKAH LAKU KAMBING KACANG (Effect of feeding silage made of different ratio of kume grass and wild markisa leaves on feeding beahavior of male kacan - L R Kari; I Gusti Ngurah Jelantik; T T Nikolaus (Universitas Nusa Cendana, 2021)
This research aimed to study the effect of feeding silage of kume grass and Pasiflora foetida leaves differing in their ratio on fiber intake and digestibility, rumen VFA and blood glucose concentration of male kacang goats. This study used four male kacang goats with the average body wight of 10,5 kg. This experiment followed a 4x4 Latin Square design with four treatments in four 21-day periods as replications. The treatments were M0 : silage made of 100 % kume grass, M20 : silage made of 80% kume grass + 20% Passiflora foetida, M40 : 60% kume grass + passiflora foetida 40%, M60 : 40% kume grass + 60% Passiflora foetida. Result showed that feeding silage made of different ratio of kume grass and Passiflora foetida leaves did not significantly (P>0,05) affect the length and frequency of eating, the length of rumination period as well as the length and frequency of resting period. Therefore, it can be concluded that inclusion of P. foetida in the silage mix with kume grass up to 60% is considered save as it did not affect the feeding behaviour of Kacang goats.